Digitalization and remote work on Tech employees - Tabatadze, Tamari (2024)
This study explored the effects of digitalization and remote work on technology workers, with a particular emphasis on work-life balance and job satisfaction. The COVID-19 pandemic has brought attention to the rapidly growing trend of remote work, making it crucial to understand the ways in which these developments impact the balance between work and personal life for tech professionals. This study showed both the advantages and disadvantages of remote work through in-depth interviews with twelve IT professionals in Georgia using a qualitative research methodology. The findings demonstrate that while working remotely can lead to greater flexibility, autonomy, and a better work-life balance, there are also several major drawbacks, including social isolation, communication difficulties, and a blurring of work and personal life boundaries. These dual aspects impact overall well-being and job satisfaction, demanding the development of organizational techniques to maximize the advantages of remote work environments while minimizing their drawbacks. The research contributes to the current discussion about the nature of work in the future by offering organizations recommendations and insights on how to improve remote work procedures while increasing worker satisfaction and productivity.